2016
DOI: 10.21010/ajtcam.v14i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-Inflammatory Capacity of Beta-Sitosterol in Rodent Assays

Abstract: Background: Beta-sitosterol (BS) is a compound discovered to be present in numerous plants. A number of interesting biomedical properties have been attributed to BS, including immuno-modulating and anti-inflammatory activities. Therefore, the aim of this report was to evaluate its anti-inflammatory capacity by applying various rodent experimental tests. Methods. To carry out the objective of the study we applied the methods indicated here. Two of the adopted methods were based on the passive reverse Arthus rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 44 publications
1
50
0
1
Order By: Relevance
“…Similar findings were observed on U937 AML cells, involving caspase 3 activation, and an increase in the Bax/Bcl2 ratio [58]. Other studies suggest the anti-inflammatory capacity of β-sitosterol [59], as well as its antihyperglycemic and insulin-releasing activities [60]. Other compounds in AELE remain unidentified and require further investigation.…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings were observed on U937 AML cells, involving caspase 3 activation, and an increase in the Bax/Bcl2 ratio [58]. Other studies suggest the anti-inflammatory capacity of β-sitosterol [59], as well as its antihyperglycemic and insulin-releasing activities [60]. Other compounds in AELE remain unidentified and require further investigation.…”
Section: Discussionsupporting
confidence: 75%
“…Phytosterols have been well-documented for having anti-inflammatory, antioxidant and anticancer effects [3739]. Previous studies have reported the potential anti-inflammatory activity of β-sitosterol using in vitro and in vivo models [40, 41]. Enriched content of β-sitosterol in VISPO could possibly contribute to the anti-inflammatory effect in BPH model.…”
Section: Discussionmentioning
confidence: 99%
“…Dosing Protocol: Control groups were given distilled water only. Aspirin 300 mg per 70 kg and Ibuprofen 200 mg per kg were given as standard drug in hot plate & tail flick and acetic acid induced paw-edema model respectively 10,11 . Single and double dose groups were given aqua distillate of Rosa damascena Mill.…”
Section: Materials and Methods: Selection Of Animalsmentioning
confidence: 99%